Centrally Extended α-Homoderivations on Prime and Semiprime Rings - Mahmoud M. El-Soufi; A. Ghareeb (Journal of Mathematics)
We present a new type of mappings called centrally extended α-homoderivations of a ring ℜ (i.e., a map H from ℜ into ℜ which satisfies Hx+y−Hx−Hy∈Zℜ and Hxy−HxHy−Hxαy−αxHy∈Zℜ for any x,y∈ℜ) where α is a mapping of ℜ and discuss the relationship between these mappings and other related mappings. Also, we study their effect on the center of a ring, and we give several outcomes on the commutativity of the ring.